Hotel Margarita [front and back] - Frank Aston::::::photographer:::
Sign indicates that R.W. Robertson is the proprietor of Hotel Margarita. There is also banner, likely unrelated to the hotel, in the top left that bears the name and title, 'O.S Sellers, Manager'.